Wavelet Quantile Evidence on Urbanisation, Human Capital and Economic Growth Impacts on Nigeria’s Ecological Footprint - Somoye, Oluwatoyin Abidemi; Ayobamiji, Awosusi Abraham; Akinwade, Toluwalope Seyi (Alanya Üniversitesi, 2025)
In light of growing uncertainties in the climate, it is crucial to identify what is causing environmental pressure in Nigeria. This study explores dynamic links between urbanisation, human capital accumulation economic growth and the nation’s ecological footprint (EF) from 1961 to 2020. Employing Wavelet Quantile Correlation (WQC) and Quantile-on-Quantile Granger Causality (QQGC) approaches, we capture both frequency-specific and distribution-specific dependencies neglected by linear techniques. WQC results indicate that rising urban population, expanding human capital and GDP growth dampen EF in the short- and medium-term, yet predominantly amplify EF over longer horizons; negative correlations persist for lower quantiles (0.1–0.5), highlighting heterogeneous vulnerabilities. QQGC confirms significant bidirectional causality across all quantile pairs, underscoring pervasive interdependence irrespective of economic or ecological states. Policy simulations suggest that integrating environmental education into all schooling levels, promoting renewable energy within rapidly growing cities, and decoupling growth from fossil-fuel dependence are critical for sustaining long-run environmental gains. Our evidence supports context-specific, time-phased interventions that align Nigeria’s urban transition and human capital strategy with its 2050 net-zero commitment. By revealing quantile-dependent effects, the study enriches environmental Kuznets literature and offers nuanced guidance for green development planning strategies.